Лінгво-прагматичні особливості мовлення політиків на політичних ток-шоу: гендерний аспект (на прикладі виступів Юлії Тимошенко та Арсенія Яценюка на політичному ток-шоу «Шустер Lіvе») = Linguistic and pragmatic features speech of politicians on the political talk shows: gender aspects (on the example performances of Yulia Tymoshenko and Arseniy Yatsenyuk on the political talk show „Shuster Live”) - Borodavko, Nataliya; Maslova, Yuliya; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Borodavko Nataliya, Maslova Yuliya, Zukow Walery. Лінгво-прагматичні особливості мовлення політиків на політичних ток-шоу: гендерний аспект (на прикладі виступів Юлії Тимошенко та Арсенія Яценюка на політичному ток-шоу «Шустер Lіvе») = Linguistic and pragmatic features speech of politicians on the political talk shows: gender aspects (on the example performances of Yulia Tymoshenko and Arseniy Yatsenyuk on the political talk show „Shuster Live”). Journal of Education, Health and Sport. 2016;6(5):349-368. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53160 http://ojs.ukw.edu.pl/index.php/johs/article/view/3535 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. ЛІНГВО-ПРАГМАТИЧНІ ОСОБЛИВОСТІ МОВЛЕННЯ ПОЛІТИКІВ НА ПОЛІТИЧНИХ ТОК-ШОУ: ГЕНДЕРНИЙ АСПЕКТ (НА ПРИКЛАДІ ВИСТУПІВ ЮЛІЇ ТИМОШЕНКО ТА АРСЕНІЯ ЯЦЕНЮКА НА ПОЛІТИЧНОМУ ТОК-ШОУ «ШУСТЕР LІVЕ») Linguistic and pragmatic features speech of politicians on the political talk shows: gender aspects (on the example performances of Yulia Tymoshenko and Arseniy Yatsenyuk on the political talk show „Shuster Live”) Бородавко Наталія Миколаївна Borodavko Nataliya Mykolayivna Національний університет «Острозька академія» National University „Ostrog Academy” Маслова Юлія Петрівна Maslova Yuliya Petrivna Національний університет «Острозька академія» National University „Ostrog Academy” Zukow Walery Zukow Walery UMK w Toruniu UMK in Torun У статті здійснено аналіз мовленнєвих здібностей українських політиків – Юлії Тимошенко та Арсенія Яценюка на основі їхніх виступів на політичному ток-шоу «Шустер Lіvе». На основі аналізу подано оцінку їхнім мовленнєвим здібностям та вмінням. Проведено лінгвістичний аналіз мовлення цих політиків, а результати порівняно в гендерному аспекті. Ключові слова: політичне ток-шоу, мовлення, лінгвістичний аналіз, політик, виступ, гендер. The article analyzes the speech abilities of Ukrainian politicians - Yulia Tymoshenko and Arseniy Yatsenyuk based on their performances at the political talk show "Shuster Live". Based on the analysis evaluates their speech abilities and skills. A linguistic analysis of speech of these politicians, and the results compared to the gender aspect. Keywords: political talk show broadcast, linguistic analysis, a politician, performance, gender.